PERKEMBANGAN MADRASAH TSANAWIYAH MADINATUN NAJAH DI BAWAH YAYASAN PENDIDIKAN AGAMA ISLAM RENGAT TAHUN 2006-2016 - Dini Miranda; Ridwan Melay; Tugiman MS ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Education as one of the most important sectors in the national development, be a mainstay for functioning as much as possible in an effort to improve the quality of Indonesian human life. Therefore in this case the private education play an active role in promoting education in the District Rengat Indragiri Hulu with the establishment of educational institutions under the auspices of the Foundation for Islamic Education Rengat (YPAIR) is the Foundation oldest first in Indragiri Hulu stands at 22 March 1942, starting On 25 January 1975 YPAIR merged into MTs Madinatun. The purpose of this research is to know the history and development of MTs Madinatn Najah under YPAIR in advancing education in the District Rengat Indragiri Hulu period 2006-2016. The method used is the historical method in which data were collected through observation, interviews, documentation, and literature. Data analysis using the method of writing history. When the study began filing titles proposal until the completion of thesis writers. The results showed that the MTs Madinatun Najah has developed very rapidly from a standing start in District Rengat Indragiri Hulu. The development of such an increase in facilities and infrastructure, teachers, students, and curriculum. This is not out of the efforts of MTs Madinatun Najah in improving the quality and quantity in the District Rengat Indragiri Hulu.Keywords: Education, Development, Mts Madinatun Najah, District Rengat